Efektivitas Penggunaan Media Canva dan Wayground terhadap Minat Belajar Matematika Peserta Didik pada Materi Statistika di SMA - Adelia Septina Prameslani; Suripah; Astri Wahyuni; Endang Istikomah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning interest is one of the affective factors that plays an important role in the success of mathematics learning. The low learning interest of students is often influenced by the use of less varied learning media so that media innovation is needed that can create more interesting and interactive learning. This study aims to analyze the effectiveness of using Canva media assisted by Wayground on students' interest in learning mathematics in statistics material in high school. The study used a quantitative approach with a quasi-experimental method and a Non-Equivalent Control Group Design. The research sample consisted of class X.7 as the experimental class and class X.9 as the control class selected using cluster random sampling techniques. Data were collected through a learning interest questionnaire, then analyzed using descriptive statistics and the Mann–Whitney U test with the help of IBM SPSS Statistics version 23. The results of the descriptive analysis showed that students' learning interest in the experimental class increased after learning using Canva media assisted by Wayground, while changes in the control class were relatively small. The results of the hypothesis test showed an Asymp. Sig. value. (2-tailed) of 0.022 (<0.05), which indicates a significant difference between the learning interests of students in the experimental class and the control class. Thus, it can be concluded that the use of Canva media assisted by Wayground is effective in increasing students' interest in learning mathematics in statistics material in high school.